Reliability of piles bearing capacity methods based on CPT - Giacon Junior, Admir José [UNESP]; Padovezi Rocha, Breno; Brito Fernandes, Jeferson [UNESP]; Gorla Nogueira, Caio [UNESP]; Luiz Giacheti, Heraldo [UNESP] (Coimbra University Press, 2019)
This paper presents a reliability analysis of three semi-empirical methods to predict piles bearing capacity based on the First Order Reliability Method (FORM) with the objective of assessing the probability of such methods to estimate the bearing capacity against safety. The data of 25 CPT tests were carried out in a single site was considered in this study as well as the load test performed in a 0,25 m diameter and 8 m long bored pile installed in an unsaturated tropical sandy soil in the city of Bauru, state of São Paulo. The distributions of the random variables defined by the cone tip resistance (qc) and the sleeve friction (fs) measured by the CPT, as well as the end bearing resistance (Qp,ult) and ultimate lateral friction (Ql,ult) from the pile were adjusted to a normal probability distribution by the Kolmogorov-Smirnov statistical test. The reliability analysis indicated that the most appropriate method to use for the studied case is the one proposed by Aoki & Velloso, which provided probability estimative against security of 0,16%, while the other two methods only can be used after been adjusted.
CONFIABILIDADE DE MÉTODOS DE PREVISÃO DA CAPACIDADE DE CARGA DE ESTACAS A PARTIR DE RESULTADOS DE CPT
Keywords: Bearing Capacity; FORM; Reliability